2016
DOI: 10.1002/gepi.21979
|View full text |Cite
|
Sign up to set email alerts
|

FARVATX: Family‐Based Rare Variant Association Test for X‐Linked Genes

Abstract: Although the X chromosome has many genes that are functionally related to human diseases, the complicated biological properties of the X chromosome have prevented efficient genetic association analyses, and only a few significantly associated X-linked variants have been reported for complex traits. For instance, dosage compensation of X-linked genes is often achieved via the inactivation of one allele in each X-linked variant in females; however, some X-linked variants can escape this X chromosome inactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Escape from XCI results in sex biases in gene expression and has implications for the role of the X chromosome in human diseases, including intellectual disability, autoimmune disease, and cancer [34,35,45,46,48,51]. It has been suggested that escape from XCI is a mechanism for respiratory disease pathology in COPD and that escape from XCI influences lung tissue transcription [52]. POU3F4 was the only suggested variant in the current analysis that is a transcription factor.…”
Section: Discussionmentioning
confidence: 77%
“…Escape from XCI results in sex biases in gene expression and has implications for the role of the X chromosome in human diseases, including intellectual disability, autoimmune disease, and cancer [34,35,45,46,48,51]. It has been suggested that escape from XCI is a mechanism for respiratory disease pathology in COPD and that escape from XCI influences lung tissue transcription [52]. POU3F4 was the only suggested variant in the current analysis that is a transcription factor.…”
Section: Discussionmentioning
confidence: 77%
“…For gene-level association analysis, WISARD supports six types of gene mapping file format: refFlat format, two interval formats and three direct mapping format while other toolsets support only one or two formats. In addition, WISARD has more functions for statistical analyses such as X-chromosome gene-level association analysis with the family-based dataset, FARVATx [ 30 ], and allows multi-thread analyses except few analyses such as PCA analysis and heritability with ‘--thread’ option.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, most of gene-level tests were limited to population-based samples, and few approaches available for family-based samples. PEDCMC [ 27 ], FARVAT [ 28 ], mFARVAT [ 29 ], and FARVATx [ 30 ] are implemented in WISARD. Furthermore, we provided new statistics, family-based VT and family-based SKAT-o.…”
Section: Methodsmentioning
confidence: 99%
“…Escape from XCI results in sex biases in gene expression and has implications for the role of the X chromosome in human diseases, including intellectual disability, autoimmune disease, and cancer [ 34 , 35 , 45 , 46 , 48 , 51 ]. It has been suggested that escape from XCI is a mechanism for respiratory disease pathology in COPD and that escape from XCI influences lung tissue transcription [ 52 ]. POU3F4 was the only suggested variant in the current analysis that is a transcription factor.…”
Section: Discussionmentioning
confidence: 99%